A Choquet integral-based approach for assessing the sustainability of a new waste incinerator. (1st January 2013) - Bottero, Marta; Ferretti, Valentina; Mondini, Giulio
The present paper proposes a multicriteria approach able to support decision makers in the choice of the best location for a new waste incinerator plant that has to be constructed in the Province of Torino (Italy). Three alternative sites have been compared based on different indicators that have been aggregated using the Choquet integral in order to obtain the global performance of each solution and to better highlight the tradeoffs between the aspects involved. The aim of the analysis is to study the contribution that the Choquet integral offers in sustainability assessment of undesirable facilities location problems, taking into consideration the existence of interactions among the criteria and paying particular attention to the use of quantitative indicators in the evaluation process. Mention should be made to the fact that the analysis takes into account the opinion of several experts in determining the importance of the different elements of the model.